2021
DOI: 10.1177/02692163211059340
|View full text |Cite
|
Sign up to set email alerts
|

Which factors influence the quality of end-of-life care in interstitial lung disease? A systematic review with narrative synthesis

Abstract: Background: People dying from interstitial lung disease experience considerable symptoms and commonly die in an acute healthcare environment. However, there is limited understanding about the quality of their end-of-life care. Aim: To synthesise evidence about end-of-life care in interstitial lung disease and identify factors that influence quality of care. Design: Systematic literature review and narrative synthesis. The review protocol was prospectively registered with PROSPERO (CRD42020203197). Data sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…At the individual level, our study found that sex, age, marital status, and education level were key factors associated with home deaths. This finding was consistent with previous studies, which found that death at home was more likely for individuals who were female, older, and had a higher level of education among patients with lung diseases ( 12 , 32 ). We also observed a higher likelihood of home deaths among rural residents and in regions with lower socioeconomic development status, including the lower level of GDP, number of beds in healthcare institutions, and average years of educational attainment.…”
Section: Discussionsupporting
confidence: 93%
“…At the individual level, our study found that sex, age, marital status, and education level were key factors associated with home deaths. This finding was consistent with previous studies, which found that death at home was more likely for individuals who were female, older, and had a higher level of education among patients with lung diseases ( 12 , 32 ). We also observed a higher likelihood of home deaths among rural residents and in regions with lower socioeconomic development status, including the lower level of GDP, number of beds in healthcare institutions, and average years of educational attainment.…”
Section: Discussionsupporting
confidence: 93%
“…In nonmalignant pulmonary diseases, receiving palliative care is associated with better symptom relief and quality of life, increased rate of advance care planning, death outside the hospital, and decreased burden from futile therapies and investigations in end of life. 3 , 10 , 18 , 19 , 27–30 The symptom burden and the need of palliative care in different nonmalignant pulmonary diseases are similar but the disease trajectory varies. 31 , 32 Patients with COPD may live long with advanced disease and severe breathlessness, whereas survival time is typically shorter among patients with end-stage ILD.…”
Section: Discussionmentioning
confidence: 99%
“…Symptom-alleviating medications are less often used in patients with nonmalignant diseases, and they undergo more diagnostic tests and invasive ventilation during the last year of life compared with cancer patients. 12 , 13 , 19 Specialist palliative care may decrease the number of emergency department visits, hospitalization, and end-of-life costs, but the quality of evidence is low and the most effective ways to integrate palliative care in the care of nonmalignant pulmonary diseases remain unknown. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these findings cannot be directly applicable to all patients with ILD. However, we believe the findings of this study have a degree of external validity since many patients with ILD, regardless of culture or region/countries, have been reported to die in a hospital setting [ 34 ]. Second, selection bias became a concern as the response rate was moderate (i.e., 45%).…”
Section: Discussionmentioning
confidence: 99%